Innovation's influence on working capital management and profitability: a Chinese high-tech manufacturing perspective - Zhou, Siyu; Amin Noordin, Bany Ariffin; Tunde, Matemilola Bolaji (John Wiley and Sons Inc, 2024)
This study investigates the role of corporate innovation in moderating the impact of working capital management on profitability for a Chinese high-tech manufacturing industry. Using a two-way fixed effect model and subgroup analysis, we found that net working capital (NWC) negatively impacted corporate profitability, while corporate innovation magnified the inverse association between the NWC and profitability. This moderating effect was stronger in non-state-owned enterprises (SOEs) than in SOEs, and different company sizes exhibited varying effects. This study enhances our understanding of the role of corporate innovation financial management and provides valuable insights for innovation research in emerging economies.